Discrete Wavelet Transform Based Real Time Retrieval Technique - Dr. V.M. Thakare, Dr. Zafar G. Sheikh, Dr. Nitin S. Goje (International Journal of Advanced Science and Technology, 2020)
Real time organized human face retrieval problem for large databases, is the problem of selecting an appropriate human face of interest from the trained video databases with minimum cost and maximum accuracy. This paper indicates the details of the proposed advancement and technique for feature extraction and feature matching. This paper has included proposed technique with detection, tracking, feature extraction and recognition with Discrete Wavelet Transform (DWT) using Haar transform and other implementation details.